Association between a stromal cell-derived factor 1 (SDF-1/CXCL12) gene polymorphism and microvascular disease in systemic sclerosis. Issue 3 (17th October 2008) - Manetti, M; Liakouli, V; Fatini, C; Cipriani, P; Bonino, C; Vettori, S; Guiducci, S; Montecucco, C; Abbate, R; Valentini, G; Matucci-Cerinic, M; Giacomelli, R; et al.
Abstract : Objective: To investigate the possible implication of SDF1 -3′ polymorphism in systemic sclerosis (SSc) susceptibility or clinical phenotype, or both. Methods: 150 patients with SSc and 150 controls were enrolled. Skin involvement, autoantibodies, interstitial lung disease, pulmonary arterial hypertension (PAH), scleroderma renal crisis, past and/or current skin ulcers were assessed. Genotyping was performed by PCR-RFLP. Results: Genotype distribution and allele frequency were similar in SSc and controls. SDF1 -3′A allele and SDF1 -3′GA/AA genotype frequencies were significantly higher in SSc-PAH than in SSc-non-PAH (33.3% vs 18.3%, p = 0.01) and in SSc with skin ulcers than in SSc without ulcers (27.3% vs 16.9%, p = 0.03). The SDF1 -3′A allele influenced the predisposition to SSc-related PAH (OR = 2.52, 95% CI 1.11 to 5.69, p = 0.02) and skin ulcers (OR = 2.31, 95% CI 1.18 to 4.52, p = 0.01). After adjustment for age and gender, the SDF1 -3′A allele remained a susceptibility factor for the SSc-related vascular manifestations (PAH: OR = 2.37, 95% CI 1.04 to 5.42, p = 0.04; ulcers: OR = 2.33, 95% CI 1.78 to 4.62, p = 0.01). Conclusion: The SDF1 -3′A allele is significantly associated with microvascular involvement in SSc.